Awareness Among Dentists Regarding the Role of Physical Therapy in Treating Temporomandibular Joint Disorders: a Cross-sectional Study - Hisham M. Hussein; Razan M. Alajmi; Raniya F. Alharbi; Mona S. Al-shammari; Rawabi R. Albrak; Najd S. Alrashidi (Rehabilitacja Medyczna)
Introduction: Physical therapy has an obvious role in the treatment of variable musculoskeletal disorders affecting the temporomandibular joint. Yet, many dentists are still unaware of this.Objectives: To assess the awareness of dentists in Ha’il City regarding the role of physical therapy in treating musculoskeletal problems of the temporomandibular joint.Material and Methods: A total of 82 dentists with different levels of experience were screened through the questionnaire to assess their awareness of the role of the physical therapy in treating temporomandibular joint disorders. Data collection was performed through an online questionnaire and onsite visits to private and governmental facilities providing dentistry services in Ha’il City, Saudi Arabia.Results: At the time of the study, 13.4% of the participants referred their patients to physical therapy. Among the subjects, 58.5% demonstrated lack of awareness regarding the role of physical therapy. By the end of the study, approximately 60% of the participants were willing to refer their patients to receive physical therapy services.Conclusions: Dentists in Ha’il city have a low level of awareness regarding the role of physical therapy in treating temporomandibular joint disorders. Research on the awareness of health professionals could be beneficial in improving their understanding of the role of physical therapy in treating different health problems.